High-throughput SNP genotyping by single-tube PCR with Tm-shift primers. (December 2005) - Wang, Jun; Chuang, Karen; Ahluwalia, Mandeep; Patel, Sarika; Umblas, Nanette; Mirel, Daniel; Higuchi, Russell; Germer, Soren
Despite many recent advances in high-throughput single nucleotide polymorphism (SNP) genotyping technologies, there is still a great need for inexpensive and flexible methods with a reasonable throughput. Here we report substantial modifications and improvements to an existing homogenous allele-specific PCR-based SNP genotyping method, making it an attractive new option for researchers engaging in candidate gene studies or following up on genome-wide scans. In this advanced version of the melting temperature (Tm )-shift SNP genotyping method, we attach two GC-rich tails of different lengths to allele-specific PCR primers, such that SNP alleles in genomic DNA samples can be discriminated by the Tm s of the PCR products. We have validated 306 SNP assays using this method and achieved a success rate in assay development of greater than 83% under uniform PCR conditions. We have developed a standalone software application to automatically assign genotypes directly from melting curve data. To demonstrate the accuracy of this method, we typed 592 individuals for 6 SNPs and showed a high call rate (>98%) and high accuracy (>99.9%). With this method, 6–10, 000 samples can be genotyped per day using a single 384-well real-time thermal cycler with 2–4 standard 384-well PCR instruments.